Visible light-promoted synthesis of organic carbamates from carbon dioxide under catalyst- and additive-free conditions. Issue 15 (24th July 2020) - Cheng, Ruixiang; Qi, Chaorong; Wang, Lu; Xiong, Wenfang; Liu, Hongjian; Jiang, Huanfeng
Abstract : A visible light-promoted process for the synthesis of organic carbamates from carbon dioxide was developed under catalyst- and additive-free conditions. Abstract : An efficient and environmentally friendly method for the synthesis of organic carbamates from carbon dioxide has been developed via photolysis of α-aryldiazoesters under mild conditions in the absence of any catalysts and additives. By using different solvents, a four- or three-component coupling reaction involving aryldiazoesters, amines and carbon dioxide could occur rapidly and selectively, giving a variety of structurally diverse organic carbamates in moderate to high yields.